Halal Industry Recovery of Creative Halal Industry Business After Covid-19 Pandemic - Abustani Ilyas; Ade Darmawan; Syarifuddin (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2024)
This research identifies gaps in understanding halal business adaptation strategies amid the COVID-19 pandemic, especially in the MSME sector, focusing on case studies of Yotta and Browcyl in Makassar. This study aims to explore the development of the two products' halal businesses after the pandemic, the strategies they implemented, and the application of Sharia principles in their operations. The method used is field research with a qualitative descriptive approach through interviews and thematic analysis. The results showed that Yotta and Browcyl survived and thrived through digital transformation and halal certification despite facing significant challenges such as declining production and sales. However, this study has weaknesses in the generalizability of the findings and the lack of investigation of the long-term economic impact of the strategies adopted. For future development, it is recommended that the scope of the study be expanded by including more cases from different segments of the halal creative business industry and analyzing government policies that affect the industry. Future research is expected to provide comprehensive guidance for industry players to formulate effective strategies to face future challenges and capitalize on growth opportunities.